PENGARUH PERHATIAN ORANG TUA DAN LINGKUNGAN SOSIAL TERHADAP PRESTASI BELAJAR BAHASA INDONESIA SISWA SMP N 1 LEIHITU KABUPATEN MALUKU TENGAH - Nukuhaly, Nur Apriany (LP2M IAIN Ambon, 2019)
Abstrak Parents' attention is all forms of effort, encouragement, and involvement in children's learning activities both at home and at school. The social environment is all other people or people who affect us. Indonesian learning achievement is the result of learning achieved by students after the process of learning Indonesian for a certain period (one semester) expressed in terms of grades or numbers. The purpose of this study was to determine whether or not there was an influence of parental attention on the Indonesian language learning achievement of Leihitu Middle School 1 students and whether or not there was an influence of the social environment on the Indonesian learning achievement of Leihitu Middle School 1 students. This type of research is an ex-post facto research with a quantitative approach. The population in this study were 160 students at SMP N 1 Leihitu in the odd semester of the 2018/2019 school year totaling 160 people. The sample was selected using stratified random sampling technique with a random composition so that the number of respondents was 80 students. The instruments used for data collection included questionnaires for parents 'attention, students' social environment questionnaires and student report cards. Based on the results of the study concluded that, there is an influence of parents 'attention on the learning achievement of Indonesian students of SMP N 1 Leihitu, there is an influence of the social environment on Indonesian learning achievement of students of SMP N 1 Leihitu, there is an influence of parents' attention and social environment on the achievement of learning Indonesian Leihitu Middle School 1 students with an influence of 20.8%. Keywords: parents' attention, social environment, Bahasa Indonesia learning achievement Abstrak Perhatian orang tua adalah segala bentuk usaha, dorongan, dan keterlibatan dalam kegiatan belajar anak baik di rumah maupun di sekolah. Lingkungan sosial adalah semua orang atau manusia lain yang mempengaruhi kita. Prestasi belajar bahasa Indonesia merupakan hasil belajar yang dicapai peserta didik setelah proses pembelajaran bahasa Indonesia selama masa tertentu (satu semester) yang dinyatakan dalam bentuk nilai atau angka. Tujuan penelitian ini adalah untuk mengetahui ada atau tidak pengaruh perhatian orang tua terhadap prestasi belajar bahasa Indonesia siswa SMP N 1 Leihitu dan ada atau tidak pengaruh lingkungan sosial terhadap prestasi belajar bahasa Indonesia siswa SMP N 1 Leihitu. Jenis penelitian yang digunakan adalah penelitian ex-post facto dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah siswa SMP N 1 Leihitu pada semester gasal tahun ajaran 2018/2019 berjumlah 160 orang. Sampel dipilih dengan menggunakan teknik stratified random sampling dengan komposisi acak sehingga diperoleh jumlah responden sebanyak 80 orang siswa. Instrumen yang digunakan untuk pengambilan data diantaranya angket perhatian orang tua siswa, angket lingkungan sosial siswa serta nilai rapor siswa. Berdasarkan hasil penelitian disimpulkan bahwa, ada pengaruh perhatian orang tua terhadap prestasi belajar bahasa Indonesia siswa SMP N 1 Leihitu, ada pengaruh lingkungan sosial terhadap prestasi belajar bahasa Indonesia siswa SMP N 1 Leihitu, ada pengaruh perhatian orang tua dan lingkungan sosial terhadap prestasi belajar bahasa Indonesia siswa SMP N 1 Leihitu dengan besar pengaruh sebesar 20,8%. Kata kunci: perhatian orang tua, lingkungan sosial, prestasi belajar bahasa Indonesia